A PRELIMINARY INVESTIGATION ON IMPROVING FUNCTIONAL COMMUNICATION TRAINING BY MITIGATING RESURGENCE OF DESTRUCTIVE BEHAVIOR - Fuhrman, Ashley M. (J Appl Behav Anal, 2016)
Despite the effectiveness and widespread use of functional communication training (FCT), resurgence of destructive behavior can occur if the functional communication response (FCR) contacts a challenge, such as lapses in treatment integrity. We evaluated a method to mitigate resurgence by conducting FCT using a multiple schedule of reinforcement prior to extinction. After functional analyses of 2 boys’ destructive behavior and treatment with FCT (Study 1), we compared levels of resurgence during an extinction challenge either after a typical FCT sequence or after exposure to schedule thinning in the context of a multiple-schedule arrangement (Study 2). Results for both participants suggested that schedule thinning using discriminative stimuli in a multiple schedule mitigated the resurgence of destructive behavior.